1,4-Dibromo-2,5-di-p-toluoylbenzene - He, Guang-Ke (International Union of Crystallography, 2013)
In the title compound, C(22)H(16)Br(2)O(2), which has approximate non-crystallographic inversion symmetry, the dihedral angles between the central ring and the pendant rings are 89.1 (4) and 82.4 (3)°; the dihedral angle between the pendant rings is 12.1 (4)°. In the crystal, the packing is influenced by van der Waals forces and no aromatic π–π stacking is observed.